Ensuring Trust and Safety in Online Trading: A Comprehensive Cyber Security Strategy to Safeguard Financial Transactions and Protect User Privacy (International Journal of Food and Nutritional Sciences, 2019)
The evolution of internet technologies has revolutionized traditional business services,transitioning many into online platforms. Online trading, serving as a financial hub for sharetransactions, bids, and product exchanges through computers, plays a pivotal role in thisdigital transformation. However, the indispensable B2B, B2C, and C2C transactions withinonline trading are constantly threatened by spyware, malware, hijackers, and intruders.